Initiation of a neoplasm or tumor - Mierke, Claudia (Physics of Cancer, 2018)
Chapter 1 presents the classical, tumor-biological viewpoint on the initiation of a tumor, and its further growth and proliferation, and points out the importance of the process of neoangiogenesis for reduced hypoxia in solid primary tumors, and their enhanced tumor growth and malignancy. A normal cell undergoes genetic mutations and epigenetic alterations and transforms into a malignant and aggressive cancer cell. The process of malignant cancer progression impacts cancer cell behavior and mechanical properties and supports the propagation of the main steps of cancer metastases in detail. The malignant transformation is associated with an accumulating loss of tissue homeostasis and enhanced perturbations of the entire structure and architecture of tissues causing the functional phenotypes of cancer cells, such as highly invasive cancer cells. The motility of cancer cells constitutes the focus, in particular their ability to transmigrate through barriers such as basement membranes and the endothelial-cell layers of vessels. Classical movement or sorting theories discuss and represent the importance of cancer cell properties for providing cellular motility or stalled behavior in cooperative networks such as tissues or spheroids. The hallmarks of cancer are presented from a biophysical point of view and the still missing mechanical aspect is addressed and included as a novel hallmark. Finally, mechanical properties profoundly affect the migration and invasion of cancer cells, and hence represent a critical aspect for the establishment of an altered mechanical phenotype in a distinct cancer type. The mechanical aspects are revisited throughout the later chapters of this book and hence chapter 1 builds the basis for understanding these chapters.
CRIS-Team WoS Importer:2019-08-27